Mining unstructured data to support requirements elicitation by using controlled vocabularies: A systematic mapping study (2015)
This paper presents a work-in-progress that deals with the assessment of the use of controlled vocabularies during the processes of requirements engineering, as a means to mine data from different sources (interviews, contracts, schemas and diagrams). By doing this the requirements description, analysis and comprehension is facilitated for both developers and end users. As a research methodology, we decided to use a systematic mapping study covering the last fourteen years (2000 - 2014). As far as we know, such studies have not yet been done; however, the cost incurred from errors in the requirements elicitation phase is one of the problems that is most commonly reported by the practitioners. Our study includes data on the processes of building the controlled vocabulary and assesses the productivity and quality. We are also interested in tools and techniques to classify and retrieve information. Our first findings suggest that this is an under-research area.